Relationship between protein intake and nutritional status with response therapy of intensive phase in pulmonary tuberculosis patients in Dili and Oecusse - Marques Lafo, Merita; Chandra, Dian Novita; Nurwidya, Fariz; Sequeira, Ercia Maria da Conçeição (World Nutrition Journal, 2025)
Background: Tuberculosis (TB) infection triggers a decrease in appetite and disrupts protein metabolism. Protein provides the main source of amino acids for immune system formation and tissue repair, both of which are impaired in tuberculosis patients. Intensive phase anti-tuberculosis therapy aims to boost immunity, reduce bacterial load, and improve nutritional status. Pulmonary TB is the leading cause of death in Timor Leste (94% mortality rate by 2021), yet few studies have explored the relationship between nutrition and treatment response. This study investigated the relationship between protein intake, nutritional status, and treatment response in pulmonary TB patients undergoing intensive therapy in Dili and Oecusse. Method: Using a cross-sectional study design, 104 participants were recruited using consecutive sampling. Data collection included both primary and secondary data. Analyses were conducted using the independent samples t-test, Mann-Whitney, and Fisher's Exact Test. Results: There are 66.3% at risk of malnutrition based on upper arm circumference, a mean body mass index of 17.86 kg/m². The median daily protein intake was 1.07 g/kgBW/day, with lower intake of animal protein compared to plant protein (0.44 g/kgBW/day vs. 0.59 g/kgBW/day). The study found no significant relationship between protein intake and nutritional status in response to the intensive phase therapy (p>0.05). Conclusion: There is no significant relationship between protein intake and nutritional status in response to the intensive phase therapy. Further research with a case-control study design is needed to confirm findings and evaluate factors affecting unbalanced therapy response.